Space confinement type gold catalyst as well as preparation method and application thereof
By designing a support for core-shell structure in a supported gold catalyst and accurately anchoring nanogold by deposition and precipitation, the problem of activity reduction caused by gold cluster sintering and aggregation is solved, and the catalytic activity and stability are improved.
Patent Information
- Application Number
- CN202411582344.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The supported gold catalyst is prone to inactive due to sintering and agglomeration of gold clusters during use, and is particularly obvious in propylene gas-phase epoxidation reaction.
By designing a space-limited gold catalyst with a core-shell structure in the carrier, nanogold is loaded using the microporous channel of the TS-1 titanium silicon molecular sieve, and the nanogold is accurately anchored in the pores in combination with the deposition and precipitation method to avoid sintering of gold clusters and reunite.
It effectively improves catalytic activity and stability, ensures efficient dispersion of nano-gold in the catalyst, and avoids the decrease in activity caused by the agglomeration of gold clusters in the reaction.
Smart Images

Figure CN119500235A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a spatially confined gold catalyst and a preparation method and application thereof. Background Art
[0002] Gold has always been considered an inert metal, but nano-gold has shown excellent catalytic activity in catalytic fields such as carbon monoxide oxidation reaction and propylene gas phase epoxidation reaction. Since gold is a precious metal and expensive, it is often loaded on a carrier to prepare a supported catalyst. On the one hand, the supported gold catalyst reduces the amount of active components, and on the other hand, the uniform dispersion of the active components on the carrier ensures the catalytic activity.
[0003] However, supported catalysts lose their activity during actual use due to various reasons, which are generally divided into three categories: poisoning, coking and clogging, sintering and thermal deactivation. Deactivation caused by poisoning can be achieved by removing the poisoning impurities contained in the reaction gas to prevent them from being adsorbed on the active sites of the catalyst and reducing the activity; deactivation caused by coking (carbon deposition) is the most common and common form of catalyst deactivation, and carbon-containing deposits can be gasified by water vapor or hydrogen to achieve catalyst regeneration. Catalyst deactivation caused by sintering is often irreversible. The sintering and aggregation of active components will cause them to lose their optimal catalytic size, thereby reducing catalytic activity. The phenomenon of reduced catalytic activity of supported gold catalysts due to gold cluster agglomeration is particularly significant in the gas-phase epoxidation reaction of propylene.
[0004] Therefore, how to avoid the sintering and agglomeration of gold clusters in supported catalysts and improve the catalytic activity is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a spatially confined gold catalyst and a preparation method and application thereof, wherein the spatially confined gold catalyst can limit the size of nano-gold particles loaded in the pores, thereby avoiding sintering and agglomeration of gold clusters in the pores, and effectively improving the catalytic activity.
[0006] In a first aspect, the present invention provides a spatially confined gold catalyst, comprising a carrier and nano-gold; the carrier has a core-shell structure, wherein the core is a TS-1 titanium silicalite molecular sieve, the shell is an S-1 all-silicon molecular sieve, and the nano-gold is loaded in the micropores of the TS-1 titanium silicalite molecular sieve.
[0007] In some embodiments of the present invention, the molar ratio of silicon element to titanium element in the TS-1 titanium silicalite molecular sieve is (40-100):1.
[0008] In some embodiments of the present invention, the average particle size of the TS-1 titanium silicalite molecular sieve is 300-850 nm, preferably 330-810 nm, and more preferably 330-500 nm.
[0009] In some embodiments of the present invention, the thickness of the S-1 all-silicon molecular sieve is 100-200 nm, preferably 120-160 nm.
[0010] In some embodiments of the present invention, in the spatially confined gold catalyst, the loading amount of the nano-gold is 0.2wt%-1.0wt%.
[0011] In a second aspect, the present invention provides a method for preparing the spatially confined gold catalyst according to the first aspect of the present invention, comprising the following steps:
[0012] (1) TS-1 titanium silicate molecular sieve was prepared by hydrothermal synthesis;
[0013] (2) using the TS-1 titanium silicalite as a crystal nucleus, and adopting a hydrothermal synthesis method to prepare a carrier having the TS-1 titanium silicalite as a core and the S-1 all-silicon molecular sieve as a shell;
[0014] (3) Nano-gold is loaded into the micropores of the TS-1 titanium silicalite molecular sieve of the carrier by a deposition precipitation method to obtain the spatially confined gold catalyst.
[0015] In some embodiments of the present invention, the hydrothermal synthesis method of step (1) comprises the following steps:
[0016] (a) stirring and mixing tetrapropylammonium hydroxide, tetraethyl orthosilicate, butyl titanate and a solvent to obtain a mixed solution;
[0017] (b) placing the mixed solution in a reaction vessel and performing a crystallization reaction at 160-180° C.;
[0018] (c) washing, drying and calcining the solid obtained in step (b) to obtain the TS-1 titanium silicalite molecular sieve.
[0019] In some embodiments of the present invention, in step (1), the volume ratio of tetrapropylammonium hydroxide and tetraethyl orthosilicate added is (0.1-1):1, preferably (0.3-0.5):1.
[0020] In some embodiments of the present invention, in step (1), the volume ratio of tetraethyl orthosilicate and butyl titanate added is (20-70):1, preferably (26-66):1.
[0021] In some embodiments of the present invention, after the TS-1 titanium silicalite is prepared in step (1), the following steps are further included:
[0022] The TS-1 titanium silicon molecular sieve is sequentially treated with acid and alkali, and then treated at 200-400° C. and a vacuum degree of 50-80 kPa for 1-3 hours, and then backfilled with nitrogen to normal pressure after cooling to room temperature.
[0023] The present invention uses the above-mentioned acid treatment, alkali treatment and vacuum treatment operations to better cover the outer surface of the TS-1 titanium silicon molecular sieve crystal core with the S-1 all-silicon molecular sieve shell.
[0024] In some embodiments of the present invention, the acid treatment process comprises: dispersing the TS-1 titanium silicon molecular sieve in 0.1-0.3 mol·L -1 The product is placed in a hydrochloric acid solution, stirred at 50-60°C for 40-50h, and then centrifuged, washed and dried.
[0025] In some embodiments of the present invention, the alkali treatment process comprises: dispersing the acid-treated TS-1 titanium silicon molecular sieve in 0.1-0.3 mol·L -1 The mixture was added to an aqueous ammonia solution and stirred at room temperature for 1-3 hours, then centrifuged, washed and dried.
[0026] In some embodiments of the present invention, the hydrothermal synthesis method of step (2) comprises the following steps:
[0027] (a) stirring and mixing tetrapropylammonium hydroxide, ethyl orthosilicate, a solvent and the TS-1 titanium silicon molecular sieve to obtain a mixed solution;
[0028] (b) placing the mixed solution in a reaction vessel and performing a crystallization reaction at 100-120° C.;
[0029] (c) washing, drying and calcining the solid obtained in step (b) to obtain the carrier.
[0030] In some embodiments of the present invention, after the carrier is prepared in step (2), the following steps are further included:
[0031] The carrier is treated at 200-400° C. and a vacuum degree of 0.01-1 kPa for 3-5 hours, and then backfilled to normal pressure with nitrogen after cooling to room temperature.
[0032] The present invention uses the high temperature and vacuum treatment operation to remove impurities in the micropores of the core-shell carrier so that the gold precursor can be anchored near the Ti site in the micropores during the subsequent deposition and precipitation process.
[0033] In some embodiments of the present invention, the calcination temperature is 500-600° C.; and / or the calcination time is 6-16 hours.
[0034] The present invention removes the organic template through the above calcination.
[0035] In some embodiments of the present invention, the sedimentation precipitation method in step (3) comprises the following steps:
[0036] (a) stirring and mixing chloroauric acid, a solvent and the carrier, adding an alkaline precipitant solution, adjusting the pH to 6.7-7.3, and continuing stirring for 4-10 hours;
[0037] (b) washing and drying the solid obtained in step (a) to obtain the spatially confined gold catalyst.
[0038] In some embodiments of the present invention, the added mass ratio of the carrier to the chloroauric acid is 1:(0.05-0.2).
[0039] In some embodiments of the present invention, the concentration of the alkaline precipitant solution is 0.1-1 mol·L -1 .
[0040] In some embodiments of the present invention, the alkaline precipitant in the alkaline precipitant solution is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, and cesium carbonate.
[0041] In some embodiments of the present invention, the drying process in step (3) is: drying overnight at room temperature and a vacuum degree of 20-50 kPa.
[0042] The present invention uses the above-mentioned vacuum condition to dry in order to accelerate the drying process at room temperature.
[0043] In some embodiments of the present invention, the solvent comprises water and / or ethanol.
[0044] The third aspect of the present invention provides use of the spatially confined gold catalyst described in the first aspect of the present invention in a gas-phase epoxidation reaction of propylene.
[0045] In some embodiments of the present invention, the reaction atmosphere of the propylene gas phase epoxidation reaction is hydrogen, oxygen, propylene and nitrogen, and the reaction conditions are at normal pressure and 164-200°C. The spatially confined gold catalyst can be directly activated in the reaction atmosphere without the need for additional reducing atmosphere treatment.
[0046] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0047] (1) The spatially confined gold catalyst provided by the present invention has a carrier with a core-shell structure, wherein the S-1 all-silicon molecular sieve coated outside the core of the TS-1 titanium silicalite molecular sieve is used to cover the Ti sites on the outer surface of the TS-1 titanium silicalite molecular sieve, thereby avoiding the active component nano-gold being loaded on the outer surface of the core-shell carrier. The nano-gold is only loaded in the micropores of the TS-1 titanium silicalite molecular sieve, achieving orderly distribution and high dispersion of the nano-gold in the pore structure of the molecular sieve carrier, thereby avoiding sintering and agglomeration of gold clusters in the pores, and effectively improving the catalytic activity.
[0048] (2) The preparation method provided by the present invention utilizes a deposition precipitation method to precisely anchor the active component nano-gold in the vicinity of the tetracoordinated Ti in the microporous channels of the TS-1 titanium silicalite molecular sieve, and the Ti sites existing on the outer surface of the TS-1 titanium silicalite molecular sieve are coated by an S-1 all-silicon molecular sieve having the same pore structure to ensure that the nano-gold is only loaded in the microporous channels of the TS-1 titanium silicalite molecular sieve, and the size of the nano-gold clusters after activation is limited to no more than 1 nm (since the double ten-membered ring pore size of the carrier is 0.53×0.56 nm and 0.51×0.55 nm, the size of the pore intersection is about 0.9 nm). Therefore, the spatially confined gold catalyst prepared has the best catalytic size for the gas-phase epoxidation reaction of propylene, and exhibits excellent catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a transmission electron microscopy image of Au / TS-1@S-1 prepared in Example 1 of the present invention;
[0050] Figure 2 This is a performance diagram of Au / TS-1@S-1 prepared in Example 1 of the present invention for catalyzing gas-phase epoxidation of propylene;
[0051] Figure 3 This is a transmission electron microscopy image of Au / TS-1@S-1 prepared in Example 1 of the present invention after catalyzing the gas-phase epoxidation reaction of propylene;
[0052] Figure 4 A schematic diagram of the distribution of nano-gold loaded on the spatially confined gold catalyst prepared in Examples 1-4 of the present invention;
[0053] Figure 5 This is a performance diagram of Au / TS-1 prepared in Comparative Example 1 of the present invention for catalyzing gas-phase epoxidation of propylene;
[0054] Figure 6 This is a transmission electron microscopy image of Au / TS-1 prepared in Comparative Example 1 of the present invention after catalyzing the gas-phase epoxidation reaction of propylene;
[0055] Figure 7 This is a schematic diagram of the distribution of nano-gold loaded on Au / TS-1 prepared in Comparative Example 1 of the present invention;
[0056] Figure 8 This is a performance diagram of Au(J) / TS-1@S-1 prepared in comparative example 2 of the present invention for catalyzing gas-phase epoxidation of propylene. DETAILED DESCRIPTION
[0057] In the description of the present invention, it is necessary to understand that the orientation or positional relationship indicated by the terms upper, lower, etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0058] Embodiments of the present invention are described in detail below. The described embodiments are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0059] Example 1
[0060] A spatially confined gold catalyst comprises a carrier and nano-gold; the carrier has a core-shell structure, wherein the core is TS-1 titanium silicalite molecular sieve, the shell is S-1 all-silicon molecular sieve, and the nano-gold is loaded in the micropores of the TS-1 titanium silicalite molecular sieve.
[0061] The preparation method of the spatially confined gold catalyst of this example comprises the following steps:
[0062] (1) 14.7 mL of tetrapropylammonium hydroxide, 35 mL of deionized water, 30 mL of ethyl orthosilicate and 1.15 mL of butyl titanate were stirred and mixed at room temperature, heated to 80° C. and stirred for 0.5 h, and then the mixture was transferred to a reactor and crystallized at 170° C. for 24 h; after cooling, the mixture was centrifuged, washed with water and dried to obtain a white solid, which was then placed in a muffle furnace and calcined at 550° C. for 16 h to obtain TS-1 titanium silicon molecular sieve;
[0063] (2) Take 2.3 g of TS-1 titanium silicalite prepared in step (1) and disperse it in 50 mL of 0.1 mol·L -1 The mixture was stirred at 50 °C for 44 h in a hydrochloric acid solution, then centrifuged, washed with water, dried, and dispersed in 50 mL of 0.1 mol·L -1 In an ammonia solution, stir at room temperature for 1 hour, then centrifuge, wash with water, and dry, and then treat at 200°C and a vacuum degree of 50 kPa for 2 hours. After cooling to room temperature, use nitrogen to backfill to normal pressure;
[0064] (3) The TS-1 titanium silicalite treated in step (2), 53 mL of deionized water and 10.2 mL of tetraethyl orthosilicate were stirred and mixed at room temperature, and then 1.23 mL of tetrapropylammonium hydroxide and 9 mL of anhydrous ethanol were added. The mixture was heated to 60° C. and stirred for 1 hour. The mixture was transferred to a reactor and crystallized at 100° C. for 20 hours. After cooling, the mixture was centrifuged, washed with water and dried to obtain a white solid. The solid was then placed in a muffle furnace and calcined at 550° C. for 16 hours to obtain a carrier with TS-1 titanium silicalite as the core and S-1 all-silicon molecular sieve as the shell (referred to as TS-1@S-1 carrier);
[0065] (4) 1.0 g of the TS-1@S-1 carrier prepared in step (3) was treated at 350° C. and a vacuum degree of 1 kPa for 4 h, and then backfilled to normal pressure with nitrogen after cooling to room temperature; then mixed with 0.1 g of chloroauric acid and 20 mL of deionized water, and magnetically stirred for 0.5 h, and then 0.5 mol·L -1 Cesium carbonate aqueous solution was added to adjust the pH value of the suspension to 7, and stirring was continued for 4 hours; after centrifugation and water washing, it was placed in a vacuum drying oven and dried overnight at room temperature and a vacuum degree of 30 kPa to obtain a spatially confined gold catalyst (denoted as Au / TS-1@S-1 catalyst).
[0066] Example 2
[0067] The difference from Example 1 is that in Example 2, the Si / Ti molar ratio can be adjusted by changing the addition amount of tetraethyl orthosilicate and butyl titanate in the preparation step (1); specifically, the addition amount of tetraethyl orthosilicate in Example 2 is 30 mL, and the addition amount of butyl titanate is 0.46 mL, and TS-1 titanium silicon molecular sieve is obtained. The remaining raw materials, addition amounts and preparation steps are the same as those in Example 1.
[0068] Example 3
[0069] The difference from Example 1 is that in Example 3, the size of the synthesized grains can be regulated by changing the addition amount of tetrapropylammonium hydroxide and tetraethyl orthosilicate in the preparation step (1); specifically, the addition amount of tetrapropylammonium hydroxide in Example 3 is 8.8 mL, and the addition amount of tetraethyl orthosilicate is 30 mL, and TS-1 titanium silicon molecular sieve is obtained. The remaining raw materials, addition amounts and preparation steps are the same as those in Example 1.
[0070] Example 4
[0071] The difference from Example 1 is that after Example 4 obtains the TS-1@S-1 carrier through step (3), the acid treatment, alkali treatment and high temperature assisted by 50 kPa vacuum treatment in step (2) are repeated with the TS-1@S-1 carrier as a raw material, and the hydrothermal synthesis method in step (3) continues to coat a layer of S-1 all-silicon molecular sieve on the outer surface of the TS-1@S-1 carrier, thereby obtaining a carrier with TS-1 as the core and a double-layer S-1 shell structure, that is, a core-shell carrier with a thicker S-1 shell is obtained. The remaining raw materials, addition amounts and preparation steps are the same as those in Example 1.
[0072] like Figure 1 As shown, the transmission electron microscopy image of the Au / TS-1@S-1 catalyst prepared in Example 1 shows that the TS-1@S-1 carrier is a core-shell structure, and no obvious nano-gold particles are observed on the outer surface. The structures of the Au / TS-1@S-1 catalysts prepared in Examples 2-4 are similar to the structure of the Au / TS-1@S-1 catalyst prepared in Example 1.
[0073] The main parameters of the preparation process of Examples 1-4 are shown in Table 1.
[0074] Table 1
[0075]
[0076] Comparative Example 1
[0077] The conventional loading method was used to prepare the nano-gold loaded catalyst Au / TS-1. The preparation process of the catalyst is as follows:
[0078] 1.0 g of TS-1 titanium silicalite prepared in step (1) of Example 1 was treated at 350° C. and a vacuum degree of 1 kPa for 4 h, and then backfilled with nitrogen to normal pressure after cooling to room temperature; then mixed with 0.1 g of chloroauric acid and 20 mL of deionized water, and magnetically stirred for 0.5 h, and then 0.5 mol·L -1 Cesium carbonate aqueous solution, adjust the pH value of the suspension to 7 and continue stirring for 4 hours; after centrifugation and water washing, place it in a vacuum drying oven and dry it overnight at room temperature and a vacuum degree of 30 kPa to obtain Au / TS-1 catalyst.
[0079] Comparative Example 2
[0080] The core-shell carrier-supported catalyst Au(J) / TS-1@S-1 was prepared by impregnation method. The preparation process of the catalyst is as follows:
[0081] Take 1.0 g of the TS-1@S-1 carrier prepared in step (3) of Example 1, treat it at 350° C. and a vacuum degree of 1 kPa for 4 h, cool it to room temperature and then backfill it to normal pressure with nitrogen; then mix it thoroughly with 0.01 g of chloroauric acid and 2 mL of deionized water, place it in a vacuum drying oven, and dry it overnight at room temperature and a vacuum degree of 30 kPa to obtain an Au(J) / TS-1@S-1 catalyst; wherein the loading amount of nanogold is about 0.4 wt%, which is the same as the loading amount of nanogold in Example 1.
[0082] Catalyst performance test
[0083] The catalysts prepared in Examples 1-4 and Comparative Examples 1-2 were used as test samples.
[0084] The performance test process of the catalyst is as follows: 0.15g of catalyst with a size of 60-80 mesh is loaded into a fixed bed tubular reactor with an inner diameter of 8mm; the reaction gas composition is 3.5mL·min -1 Propylene, 3.5 mL min -1 Hydrogen, 3.5 mL min -1 Oxygen and 24.5 mL min -1 The catalyst was heated at 1 °C min -1 The reaction was carried out at a heating rate from room temperature to 200°C, and the tail gas was detected by gas chromatograph and quantitatively analyzed.
[0085] The Au / TS-1@S-1 catalyst prepared in the embodiment of the present invention is gradually reduced into Au nanoclusters by the reaction atmosphere (10% H2 / 10% O2 / 10% C3H6 / 70% N2) during the temperature test, and together with the tetracoordinated Ti sites nearby, it serves as the active site for catalyzing the gas-phase epoxidation reaction of propylene.
[0086] The catalytic activity of Au / TS-1@S-1 catalyst prepared in Example 1 for gas-phase propylene epoxidation at 200°C is as follows: Figure 2 The catalytic activity of Au / TS-1@TS-1 at the initial stage of the reaction is about 145 g PO ·h -1 kg cat -1 The average decay rate within 50 hours is 0.12%·h -1 .
[0087] like Figure 3As shown in the transmission electron micrograph of Au / TS-1@S-1 in Example 1 after catalyzing the gas-phase epoxidation of propylene, no obvious large-sized gold particles were observed on the outer surface of the TS-1@S-1 core-shell carrier, and it can be seen that the loaded nano-gold was well confined in the micropores of the core of the TS-1 titanium silicalite molecular sieve. The distribution diagram of the nano-gold loaded on the core-shell catalyst prepared in Examples 1-4 is shown in Figure 4 shown.
[0088] The catalytic activity of Au / TS-1 catalyst prepared in Comparative Example 1 for gas-phase epoxidation of propylene at 200°C is as follows: Figure 5 As shown. The catalytic activity of Au / TS-1 at the initial stage of the reaction is about 80g PO ·h -1 kg cat -1 The average decay rate within 50 hours is 0.45%·h -1 .
[0089] Similar to the example, the Au / TS-1 catalyst was gradually reduced into Au nanoclusters by the reaction atmosphere (10% H2 / 10% O2 / 10% C3H6 / 70% N2) during the temperature test, and together with the nearby four-coordinated Ti sites, they served as active sites for catalyzing the gas-phase epoxidation of propylene.
[0090] like Figure 6 As shown in FIG. 1 , the transmission electron microscopy image of Au / TS-1 in Comparative Example 1 after catalyzing the gas-phase epoxidation of propylene shows that larger nano-gold particles are observed on the outer surface of the TS-1 carrier, which is the main reason for the decrease in catalytic activity. The distribution diagram of the nano-gold loaded on Au / TS-1 is shown in FIG. Figure 7 As shown, the gold nanoparticles on the outer surface of TS-1 migrate and aggregate to form larger gold particles and lose their catalytic activity. Therefore, compared with the conventional gold nanoparticle catalyst Au / TS-1, the spatially confined catalyst Au / TS-1@S-1 of the present invention has a better spatial confinement effect on the Au nanoclusters loaded in the micropores of the TS-1 core, thereby showing better catalytic activity and stability.
[0091] The catalytic activity of Au(J) / TS-1@S-1 catalyst prepared in Comparative Example 2 for gas-phase epoxidation of propylene at 200°C is as follows: Figure 8 The catalytic activity of Au(J) / TS-1@S-1 at the initial stage of the reaction is about 78 g PO ·h -1 kg cat -1 The average decay rate within 50 hours is 0.81%·h -1 The performance decayed seriously in the initial stage of the reaction, and the average decay rate from 0 to 5 hours was as high as 4.62%·h-1 It can be seen that the nano-gold catalyst loaded by the impregnation method failed to achieve the same good spatial confinement effect as the Au / TS-1@S-1 prepared by the deposition precipitation method in Example 1.
[0092] The test results of the above catalyst performance are shown in Table 2.
[0093] Table 2
[0094] Group <![CDATA[Catalytic activity at the initial stage of the reaction (g PO ·h -1 ·kg cat -1 )]]> <![CDATA[Average decay rate within 50 h (%·h -1 )]]> Example 1 145 0.12 Example 2 138 0.11 Example 3 92 0.17 Example 4 83 0.08 Comparative Example 1 80 0.45 Comparative Example 2 78 0.81
[0095] In conjunction with Table 1, it can be seen from the catalytic activity of Examples 1-4 in Table 2 that the core-shell catalysts loaded with nano-gold by the deposition precipitation method in Examples 1-4, wherein the Si / Ti molar ratio of the TS-1 titanium silicon molecular sieve, the average particle size of the TS-1 titanium silicon molecular sieve, and the thickness of the S-1 all-silicon molecular sieve, will affect the propylene gas phase epoxidation performance of the spatially confined gold catalyst. The Si / Ti molar ratio of the TS-1 titanium silicon molecular sieve affects the loading amount of the gold active component on the core-shell carrier, and the average particle size of the TS-1 titanium silicon molecular sieve and the thickness of the S-1 all-silicon molecular sieve affect the mass transfer process of the reactants in the microporous channels. Therefore, the catalytic activity of the spatially confined gold catalyst prepared in Example 1 is relatively better.
[0096] It can be seen from Table 2 that the core-shell catalysts loaded with nanogold by the deposition precipitation method in Examples 1-4 have an average attenuation rate within 50 hours that is significantly smaller than that of the non-confined gold catalysts prepared in Comparative Examples 1-2, indicating that the confined gold catalysts loaded with nanogold by the deposition precipitation method have excellent catalytic stability.
[0097] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A spatially confined gold catalyst, characterized in that: It comprises a carrier and nano-gold; the carrier has a core-shell structure, wherein the core is TS-1 titanium silicalite molecular sieve, the shell is S-1 all-silicon molecular sieve, and the nano-gold is loaded in the micropores of the TS-1 titanium silicalite molecular sieve.
2. The spatially confined gold catalyst according to claim 1, characterized in that: The molar ratio of silicon element to titanium element in the TS-1 titanium silicalite molecular sieve is (40-100):
1.
3. The spatially confined gold catalyst according to claim 1, characterized in that The average particle size of the TS-1 titanium silicalite molecular sieve is 300-850 nm.
4. The spatially confined gold catalyst according to claim 1, characterized in that The thickness of the S-1 all-silicon molecular sieve is 100-200 nm.
5. The spatially confined gold catalyst according to claim 1, characterized in that: In the spatially confined gold catalyst, the loading amount of the nano-gold is 0.2wt%-1.0wt%.
6. The method for preparing the spatially confined gold catalyst according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) TS-1 titanium silicate molecular sieve was prepared by hydrothermal synthesis; (2) using the TS-1 titanium silicalite as a crystal nucleus, and adopting a hydrothermal synthesis method to prepare a carrier having the TS-1 titanium silicalite as a core and the S-1 all-silicon molecular sieve as a shell; (3) Nano-gold is loaded into the micropores of the TS-1 titanium silicalite molecular sieve of the carrier by a deposition precipitation method to obtain the spatially confined gold catalyst.
7. The preparation method according to claim 6, characterized in that: The hydrothermal synthesis method of step (1) comprises the following steps: (a) stirring and mixing tetrapropylammonium hydroxide, tetraethyl orthosilicate, butyl titanate and a solvent to obtain a mixed solution; (b) placing the mixed solution in a reaction vessel and performing a crystallization reaction at 160-180° C.; (c) washing, drying and calcining the solid obtained in step (b) to obtain the TS-1 titanium silicalite molecular sieve.
8. The preparation method according to claim 6, characterized in that: The hydrothermal synthesis method of step (2) comprises the following steps: (a) stirring and mixing tetrapropylammonium hydroxide, ethyl orthosilicate, a solvent and the TS-1 titanium silicon molecular sieve to obtain a mixed solution; (b) placing the mixed solution in a reaction vessel and performing a crystallization reaction at 100-120° C.; (c) washing, drying and calcining the solid obtained in step (b) to obtain the carrier.
9. The preparation method according to claim 6, characterized in that: The sedimentation precipitation method of step (3) comprises the following steps: (a) stirring and mixing chloroauric acid, a solvent and the carrier, adding an alkaline precipitant solution, adjusting the pH to 6.7-7.3, and continuing stirring; (b) washing and drying the solid obtained in step (a) to obtain the spatially confined gold catalyst.
10. Use of the spatially confined gold catalyst according to any one of claims 1 to 5 in gas-phase epoxidation of propylene.
Citation Information
Patent Citations
Ion exchange resin supported nano gold catalyst and preparation method thereof
CN107983417A
Method for improving dispersity of gold nanoparticles of titanium silicalite molecular sieve supported gold catalyst and application
CN115283011A